On the Well-Posedness of A High Order Convective Cahn-Hilliard Type Equations - Giuseppe Maria Coclite; Lorenzo di Ruvo (Algorithms, 2020)
High order convective Cahn-Hilliard type equations describe the faceting of a growing surface, or the dynamics of phase transitions in ternary oil-water-surfactant systems. In this paper, we prove the well-posedness of the classical solutions for the Cauchy problem, associated with this equation.